Prediction of Microcystis Blooms Based on TN:TP Ratio and Lake Origin - Yoshimasa Amano; Motoi Machida; Hideki Tatsumoto; Dennis George; Sharon Berk; Kazuo Taki (The Scientific World Journal)
We evaluated the relationship between TN:TP ratio and Microcystis growth via a database that includes worldwide lakes based on four types of lake origin (dammed, tectonic, coastal, and volcanic lakes). We used microcosm and mesocosm for the nutrient elution tests with lake water and four kinds of sediment (nontreated, MgO sprinkling treated, dissolved air flotation [DAF] treated, and combined treated sediment) in order to control TN:TP ratio and to suppress Microcystis growth. Microcystis growth was related to TN:TP ratio, with the maximum value at an optimum TN:TP ratio and the minimum values when the TN:TP ratios reached to 0 or ∞. The kurtosis of the distribution curve varied with the type of lake origin; the lowest kurtosis was found in dammed lakes, while the highest was found in volcanic lakes. The lake trophic state could affect the change in the kurtosis, providing much lower kurtosis at eutrophic lakes (dammed lakes) than that at oligotrophic lakes (volcanic lakes). The relationship between TN:TP ratio and Microcystis growth could be explained by the nutrient elution tests under controlled TN:TP ratios through the various sediment treatments. A significant suppression of Microcystis growth of 70% could be achieved when the TN:TP ratios exceeded 21. Lake origin could be regarded as an index including morphological and geographical factors, and controlling the trophic state in lakes. The origin rather than trophic state for lakes could be considered as an important factor of TN:TP influences on Microcystis growth.